2022
DOI: 10.1177/17590914221087817
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenic Sphingolipid Psychosine is Secreted in Extracellular Vesicles in the Brain of a Mouse Model of Krabbe Disease

Abstract: Psychosine exerts most of its toxic effects by altering membrane dynamics with increased shedding of extracellular vesicles (EVs). In this study, we discovered that a fraction of psychosine produced in the brain of the Twitcher mouse, a model for Krabbe disease, is associated with secreted EVs. We evaluated the effects of attenuating EV secretion in the Twitcher brain by depleting ceramide production with an inhibitor of neutral sphingomyelinase 2, GW4869. Twitcher mice treated with GW4869 had decreased overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…No change in the number of OL lineage cells in the perinatal brains of Syn1Cre; Galc flox/− indicates that the myelin phenotype in Syn1Cre; Galc flox/− may not be due to loss of gliogenesis but presumably toxicity from GALC-deficient neurons such as psychosine ( Fig 7H ). A recent publication from Reiter and colleagues [ 42 ] demonstrated appreciable levels of psychosine in extracellular vesicles of the twitcher mouse, providing proof of concept to the idea that psychosine of neuronal origin may influence the health of neighboring cells. Alternatively, in line with recent studies showing that electrically active neurons can signal nearby OPCs to initiate proliferation and/or differentiation to mature OLs in response to environmental cues [ 43 ], it is possible that deletion of Galc in neurons alters neuronal activity and its effect on myelination.…”
Section: Discussionmentioning
confidence: 97%
“…No change in the number of OL lineage cells in the perinatal brains of Syn1Cre; Galc flox/− indicates that the myelin phenotype in Syn1Cre; Galc flox/− may not be due to loss of gliogenesis but presumably toxicity from GALC-deficient neurons such as psychosine ( Fig 7H ). A recent publication from Reiter and colleagues [ 42 ] demonstrated appreciable levels of psychosine in extracellular vesicles of the twitcher mouse, providing proof of concept to the idea that psychosine of neuronal origin may influence the health of neighboring cells. Alternatively, in line with recent studies showing that electrically active neurons can signal nearby OPCs to initiate proliferation and/or differentiation to mature OLs in response to environmental cues [ 43 ], it is possible that deletion of Galc in neurons alters neuronal activity and its effect on myelination.…”
Section: Discussionmentioning
confidence: 97%
“… 45 Removal of β-galactose from β-galactosylceramide, leads to the formation of the oncosuppressor metabolite ceramide, 46 which may play a role in tumor growth and differentiation. 47 GalSph and GlcSph, lipids that disrupt the lysosomes, play definitive roles in cancer therapy. 48 Consequently, they may contribute to the development of multidrug-resistance by cancer cells.…”
Section: Role Of Galc In Cancermentioning
confidence: 99%
“…Moreover, several findings are emerging in the literature concerning new aspects of KD’s pathogenesis that cannot be explained by PSY accumulation alone. This theory is evolving, and one of the latest aspects pointed out is that PSY is secreted in extracellular vesicles in the brain of the twitcher mouse (the natural KD murine model); however, substrate reduction therapy can increase lifespan but not rescue the phenotype [ 13 ]. Alterations were found in the structure and function of the brain endothelium of KD patients and twitcher mice, in vivo and in vitro, revealing an increased permeability of the vessels [ 14 ]; importantly, studies on zebrafish embryos [ 15 ] and on human endothelial cells [ 16 ] suggested that these effects were not PSY-dependent.…”
Section: Introductionmentioning
confidence: 99%